Midlife Cardiorespiratory Fitness, Incident Cancer, and Survival After Cancer in Men: The Cooper Center Longitudinal Study - Lakoski, Susan G. (JAMA Oncol, 2015)
IMPORTANCE: Cardiorespiratory fitness (CRF) as assessed by formalized incremental exercise testing is a strong independent predictor of numerous chronic diseases but has received little attention as a predictor of incident cancer or survival following a diagnosis of cancer. OBJECTIVE: To assess the association between midlife CRF and incident cancer and survival following a cancer diagnosis. DESIGN: Prospective, observational cohort study. SETTING: Preventive medicine clinic PARTICIPANTS AND EXPOSURES: The prospective, observational cohort study included 13,949 community-dwelling men who had a baseline fitness examination. All men completed a comprehensive medical examination, a cardiovascular risk factor assessment, and incremental treadmill exercise test to evaluate CRF. We utilized age-sex specific distribution of treadmill duration from the overall CCLS population to define fitness groups as low (lowest 20%), moderate (middle 40%), and high (upper 40%) fit groups. The adjusted multivariable model included: age, exam year, body mass index, smoking, total cholesterol, systolic blood pressure, diabetes, fasting glucose. MAIN OUTCOME MEASURES: (1) Incident prostate, lung, and colorectal cancer, and (2) all-cause mortality and cause-specific mortality among men who developed cancer are Medicare age (on or after age 65 years). RESULTS: Compared to low CRF, the adjusted hazard ratio (HR) for incident lung, colorectal, and prostate cancer among men with high CRF was 0.45 (95% CI: 0.29-0.68), 0.56 (95% CI: 0.36-0.87), 1.22 (95% CI: 1.02-1.46), respectively. Among those diagnosed with cancer at Medicare age (65 years), high CRF in mid-life was associated with an adjusted 36% (HR 0.64, 95% CI: 0.45-0.93) risk reduction in all cancer related deaths and a 69% reduction in cardiovascular disease mortality following a cancer diagnosis (HR 0.31, 95% CI: 0.15-0.62) compared to low fit men in mid-life. CONCLUSIONS AND RELEVANCE: There is a strong inverse relationship between midlife CRF and incident lung and colorectal cancer but not prostate cancer. High mid-life CRF is also protective against the risk of cause-specific mortality in those diagnosed with cancer at Medicare age.